Feasibility Analysis of the Fishing Equipment Business Bagan Perahu KM. Sembari 05 at Fish Landing Base (PPI) Air Bangis, Sungai Beremas District Pasaman Barat Regency, West Sumatra Province - Rantika, Tri; Isnaniah, Isnaniah; Nasution, Polaris (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2023)
The feasibility analysis of the boatlift net business aims to find out whether the KM Sembari 05 Bagan perahu net with a boat weight of 30 GT is feasible to be made into a fishing business or not based on business feasibility analysis. The method used in this research is a survey method by making direct observations in the field by looking at fishing activities using Bagan perahu fishing gear. Investment costs incurred for the operation of the KM. Sembari 05 Bagan perahu net is IDR 1,005,400,000; production costs for 1 year for fixed costs and operational costs are IDR. 1,502,292,400. While the gross income earned for 1 year Rp. 2,315,731,000 and a net income of IDR. -556,601,900/year. KM. Sembari 05 ship has a payback period of the capital of 1 year 9.6 months, which means a payback period of at least 1 year 9.6 months is required from the total service life of the KM Bagan perahu while 05 is 20 years